Important analyzing parameters in the assessment of salt tolerance in plants - Xuan, Hoang Thi Lan; Thao, Nguyen Phuong (Vietnam Journal of Biotechnology, 2021)
Maximal crop performance potential and land area suitable for cultivation are usually restricted by adverse environmental conditions. Among the abiotic factors, salinity stress is considered as one of the main threats, which causes ionic toxicity, dehydration and oxidative stresses on the plants. Alarmingly, the impact of salinity is predicted to be more severe in the forthcoming years due to global warming. Therefore, development of new cultivars with better salinity resistance with mimimized yield penalty under the adverse condition, either by breeding or genetic engineering approach, has attracted a great attention from the scientists. In this review, important parameters used in evaluation of plant resistance ability against salinity stress are discussed, which highlights the necessity to obtain multi-sets of biological data ranging from analyses of morphological alterations to physiological, biochemical and molecular responses, as well as by performing -omics studies to find out network of salinity-responsive pathways. Literature review also demonstrates that the relevance of salinity condition setup in terms of concentration and duration is required in experimental design. Furthermore, recent investigations on genome duplication, activities of non-coding sequence or epigenetics also reveal their regulatory roles in shaping plant response and tolerance degree toward salinity stress. Collection of such data not only contributes to widen scientific understanding of plant response mechanisms and adaptation to this stress factor but also facilitates the identification of important genes associating with plant tolerance to salinity. Therefore, the presented information could be used as a reference for the salinity stress-related studies serving for crop innovation and transgene function characterization.